Citizen's charter an assessment of contributions to frontline service delivery - Perante-Calina, Lizan E. (Philippine Journal of Public Administration, 2015)
An important policy measure that the Philippine government has recently introduced is the improvement of frontline service delivery through Republic Act 9485, otherwise known as the Anti-Red Tape Act (ARTA) of 2007. The ARTA, as part of the public sector reforms sweeping the bureaucracy both at the national and local levels, features novel strategies and mechanism aimed to improve efficiency in the delivery of frontline services through simplified transactions, feedback mechanisms, elimination of red tape and fixing activities, and professionalizing the bureaucracy. This article delves into the politico-administrative system that uphold the principles of accountability, transparency, citizen engagement, efficiency, and effectiveness. The focus of the study is the assessment of the contributions of the Citizen's Charter in governance after seven years of implementation, particularly on how frontline services are delivered to citizen-clients.